Correlation ofo-Ps annihilation properties with catalytic activities of palladium species immobilized on functionalized MCM-41 supports. (January 2023) - Su, Baogang; Pan, Hui; Li, Linbo; Shao, Linjun; Qi, Chenze; Zhou, Shujing; Li, Jinjing
Abstract: Design and preparation of highly active and stable supported palladium catalysts have garnered increased attention for their easy separation and reusability. Herein, MCM-41 mesoporous materials functionalized by four different amino functional groups were synthesized by using four commercially available siloxanes and then used to support palladium catalysts. The Fourier transform infrared spectroscopy (FT-IR) was used to analyze the chemical structures of functionalized MCM-41 supports. The thermogravimetric analysis (TGA) and element analysis (EA) were employed to determine the grafting densities of functional groups on MCM-41 supports. The mesoporous structures of functionalized MCM-41 supports and dispersion of palladium species were characterized by high resolution transmission electron microscopy (TEM) and X-ray diffraction patterns (XRD). A study of the materials using positron annihilation lifetime spectroscopy (PALS) reveals the different ortho-positronium ( o -Ps) annihilation properties of the supported palladium species on the four supports. Meanwhile, the catalytic activities of supported palladium species on the four supports were evaluated by the Heck reactions of iodobenzene with n-butyl acrylate. At last, the annihilation properties of the supported palladium species on the four supports were successfully correlated with their catalytic activities. The result suggests a facile method to determine and predict the catalytic activities of supported palladium species by using PALS, which may hold great potential in the preparation of rationally designed and highly active supported palladium catalysts. Graphical abstract: Image 1 Highlights: The o -Ps annihilation constants of palladium species were measured by PALS. The catalytic activities of palladium species were determined by Heck reaction. The catalytic activities were well correlated with the o -Ps annihilation constants. A novel method was developed to predicate the catalytic activities of palladium.